Transforming Bangladesh into a middle income economy - Ahmed, Sadiq (Delhi : Macmilan India, 2005)
Contributed articles on economic reform process and growth in Bangladesh.
Includes statistical tables.
Includes bibliographical references and index.
Donated By Akbar Ali Khan
Keywords: Economics; Bangladesh -- Economic policy; Bangladesh -- Economic policy -- Statistics; Bangladesh -- Economic conditions; Bangladesh -- Economic conditions -- Statistics